Four methods for determining the composition of trace radioactive surface contamination of low-radioactivity metal - O'Keeffe, H; Burritt, T; Cleveland, B; Doucas, G; Gagnon, N; Jelley, N; Kraus, C; Lawson, I; Majerus, S; McGee, SR; Myers, A; Poon, A; et al. (2011)
Four methods for determining the composition of low-level uranium- and thorium-chain surface contamination are presented. One method is the observation of Cherenkov light production in water. In two additional methods a position-sensitive proportional counter surrounding the surface is used to make both a measurement of the energy spectrum of alpha particle emissions and also coincidence measurements to derive the thorium-chain content based on the presence of short-lived isotopes in that decay chain. The fourth method is a radiochemical technique in which the surface is eluted with a weak acid, the eluate is concentrated, added to liquid scintillator and assayed by recording betaalpha coincidences. These methods were used to characterize two 'hotspots' on the outer surface of one of the 3+He proportional counters in the Neutral Current Detection array of the Sudbury Neutrino Observatory experiment. The methods have similar sensitivities, of order tens of ng, to both thorium- and uranium-chain contamination. © 2011 Elsevier B.V. All rights reserved.